2013
DOI: 10.4236/jwarp.2013.56064
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Investigation Using Geoelectrical Method: A Case Study of the Western Region of Cameroon

Abstract: A geoelectrical survey using the electrical resistivity method was carried out in some villages in the western region of Cameroon to investigate the sub-surface layers and evaluate the characteristics of aquifers. The direct current electrical resistivity method was utilized for the present study. Applying the Schlumberger array, a total of twenty four (24) Vertical Electrical Soundings (VES) were conducted. Quantitative and qualitative interpretations of data were carried out to determine the nature and thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 6 publications
(6 reference statements)
3
7
0
Order By: Relevance
“…The different observations made show that the shape of a VES curve does not depend essentially on the lithological nature, but on the structure of the ground (thickness and number of layers, degree of alteration and presence or absence of fractures). This observation is consistent with the observations of many authors [23,24,29]; both in the basement area and in the sedimentary area. In addition to these two main factors, there is the topography which, according to [30], is the main factor which would influence the shape of the VES curves, especially within a terrain whose lithological nature is homogeneous.…”
Section: Diversity Of Ves Curves and Borehole Productivitysupporting
confidence: 94%
See 1 more Smart Citation
“…The different observations made show that the shape of a VES curve does not depend essentially on the lithological nature, but on the structure of the ground (thickness and number of layers, degree of alteration and presence or absence of fractures). This observation is consistent with the observations of many authors [23,24,29]; both in the basement area and in the sedimentary area. In addition to these two main factors, there is the topography which, according to [30], is the main factor which would influence the shape of the VES curves, especially within a terrain whose lithological nature is homogeneous.…”
Section: Diversity Of Ves Curves and Borehole Productivitysupporting
confidence: 94%
“…The frequency and length of fractures in these granitoids constitute the vulnerability points in which water infiltrations occur, and then favour the productivity of the aquifers in the area. The curves shape obtained are similar to the anomalies identified in volcanic and cristalline area in Cameroon [23,24] and on the basement area made of granitoï ds in Ivory Coast [25][26][27] and Nigeria [28]. This suggested that shape of the curves is influenced by the topography and the structure of the field [24].…”
Section: Diversity Of Ves Curves and Borehole Productivitysupporting
confidence: 71%
“…The fifth studied layer located between 15 and 19 m depth shows a significant variation of the resistivity (Figure 3(f)) throughout the study area which reflects the presence of clay and sandy clays. Keleko et al; reveal in west-cameroon four to five electric layers which corroborate with the present study. The difference between the both results situated on the variation of resistivities values is due to the fact that the present is made in the sedimentary zone which is not the case for their study.…”
Section: Discussion and Interpretationsupporting
confidence: 93%
“…Resistivity is the reciprocal electrical current. In most porous rock systems, ionic conduction by interstitial fluids and surface conduction at the interface between solid rock matrices and electrolytic solution are responsible for a major part of the electric current flowing through a formation (Keleko et al, 2013). Electrical Journal of Geoscience and Environment Protection This method involves the supply of direct current into the grown through a pair of current electrodes and the measurement of the resulting potential through another pair of electrodes called potential electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…The study area is characterized by fractured phreatic aquiferous formations found within the hard rock system, and the aquifer types are defined as being superimposed or isolated [15]. The weathered basement (regolith) and alkali-rich fluvial sediments constitute the aquiferous materials in the area.…”
Section: Geology and Hydrogeology Of The Study Areamentioning
confidence: 99%